143k views
2 votes
Solve g(7) given g(X)= -3x+1

User LexLythius
by
5.7k points

2 Answers

1 vote

Answer:

-20

Explanation:

Substitute 7 into the function g(x)

Since negatives "rule" positives,

7 * -3 = -21,

-21 + 1 = -20

User ColinWa
by
5.5k points
4 votes

Explanation:

that means we need to calculate the function result with x having a specific value.

for this we replace any appearance of x in the function expression by that specific value, and then we calculate.

g(x) = -3x + 1

g(7) means x = 7, and that gives us

-3×7 + 1 = -21 + 1 = -20

so, g(7) = -20

User Riversun
by
5.1k points